Obstacles to the educational praxis of nurses in the Family Health Strategy - Darlisom Sousa Ferreira; Flávia Regina Souza Ramos; Elizabeth Teixeira; Wagner Ferreira Monteiro; Aldalice Pinto de Aguiar
ABSTRACT Objective: To analyze the obstacles to the educational praxis of nurses in the Family Health Strategy of the Eastern Health District, Manaus, Amazonas, Brazil. Method: Qualitative, exploratory, and descriptive study that used the Word Café technique for data production, with 26 nurses, between June and August 2018. The data were organized in the Atlas.ti8 software, and the analysis was categorical-thematic. Results: The units of analysis "Organizational Obstacles for Educational Praxis in the Family Health Strategy" and "Operational Obstacles for Educational Praxis in the Family Health Strategy" reveal difficulties, tensions, resistances and the impossibilities to adhere to emerging models of work organization, in general, and in particular, in educational work. Conclusion: What presents itself in reality as an obstacle is, at the same time, indicative of the possibility of overcoming and potentiality for co-creation of educational work as a strategy to rescue professional motivation, and an alternative on the agenda for the permanent qualification of workers and institutions.